2022
DOI: 10.15252/emmm.202115622
|View full text |Cite
|
Sign up to set email alerts
|

Dual IRE1 RNase functions dictate glioblastoma development

Abstract: The journal is waiting on the results of institutional proceedings regarding inconsistencies in Figure 8A and will update the scientific record appropriately in due course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 5 publications
1
69
0
2
Order By: Relevance
“…We have recently identified CD95 mRNA as being cleaved by IRE1 in an in vitro RNA cleavage assay 11 . To evaluate if the level of CD95 mRNA is controlled by IRE1 in a cellular context, we used the U87 GB cell line, which displays a constitutive activation of IRE1 11 . Expression of a dominant-negative (DN) form of IRE1, which represses the activation of endogenous IRE1, and thus its RNase activity 30, 31 , led to a significant increase in the basal level of CD95 mRNA ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently identified CD95 mRNA as being cleaved by IRE1 in an in vitro RNA cleavage assay 11 . To evaluate if the level of CD95 mRNA is controlled by IRE1 in a cellular context, we used the U87 GB cell line, which displays a constitutive activation of IRE1 11 . Expression of a dominant-negative (DN) form of IRE1, which represses the activation of endogenous IRE1, and thus its RNase activity 30, 31 , led to a significant increase in the basal level of CD95 mRNA ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we explored whether the activation of the RIDD and XBP1s branches of IRE1 RNase activity might correlate with CD95 mRNA expression levels in human tumours. Thus, we analysed the expression of this DR mRNA in tumours classified according to their RIDD and XBP1s gene expression signature, as defined previously 11 . This analysis revealed that XBP1s-high tumours present a significantly heightened expression of CD95, as compared to XBP1s-low tumours ( Fig 5C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations